Seventy‐two total knee arthroplasties performed in patients with haemophilia using continuous infusion. Issue 2 (2nd October 2012) - Chevalier, Y.; Dargaud, Y.; Lienhart, A.; Chamouard, V.; Negrier, C.
<x xml:space="preserve">Abstract</x> Background and Objectives Total knee replacement (TKR) is the treatment of choice in case of end‐stage knee arthropathy, the main complication of haemophilia. We report here a retrospective evaluation of 72 total knee replacement in 51 haemophilia A and B patients using continuous infusion of factor concentrates (CIFC). Materials and Methods Patients were evaluated on the basis of the following efficacy and safety criteria: range of motion, surgery‐related blood loss by three different methods, factor consumption and occurrence of short and long term complications. Results Kaplan–Meier analysis showed a removal‐free survival of TKRs of 88.4% 10 years after surgery. Most patients were satisfied with their prosthesis and described pain relief and improved mobility and better quality of life after surgery. The long term follow‐up showed a mean range of motion at 86° with a flexion deformity of 4°. The blood loss differed significantly according to the method used for measurement. No life‐threatening bleeding occurred. Twenty six haematomas (36.1%) and 2 haemarthroses (2.7%) occurred in 38.8% of cases during the first three postoperative weeks, with no significant impact on the orthopaedic outcome. The average factor consumption during hospitalization was 79 IU/kg/day for patients with haemophilia A and 99 IU/kg/day for patients with haemophilia B. Infections occurred in 4.1% of patients. One patient with severe haemophilia A developed an inhibitor. Conclusions The multidisciplinary approach and the homogeneous management of our large cohort allowed the achievement of excellent functional results. Our results confirmed previously reported data on the safety and efficacy of CIFC in situations requiring intensive factor replacement, such as TKR surgery.